The Role of Benzylpenicilloyl Epimers in Specific IgE Recognition - Mayorga, Cristobalina; Montañez, Maria I.; Najera, Francisco; Bogas, Gador; Fernandez, Tahía D.; Gil, David Rodríguez; Palacios, Ricardo; Torres, Maria J.; Vida, Yolanda; Perez-Inestrosa, Ezequiel (Frontiers in Pharmacology, 2021)
The high prevalence of allergy to β-lactam antibiotics is a worldwide issue. Accuracy of diagnostic methods is important to prove tolerance or allergy, with skin test considered the best validated in vivo method for diagnosing immediate reactions to β-lactams. Although drug provocation test is the reference standard, it cannot be performed in highly risk reactions or in those with positive skin tests. For skin tests, the inclusion of major and minor determinants of benzylpenicillin (BP) is recommended. Commercial skin test reagents have changed along time, including as minor determinants benzylpenicillin, benzylpenicilloate (BPO), and benzylpenilloate (PO). Major determinants consists of multivalent conjugates of benzylpenicilloyl coupled through amide bond to a carrier polymer, such as penicilloyl-polylysine (PPL) or benzylpenicilloyl-octalysine (BP-OL). The chemical stability of such reagents has influenced the evolution of the composition of the commercial kits, as this requirement is necessary for improving the quality and standardization of the product. In this work, we provide a detailed study of the chemical stability of BP determinants. We observed that those structures suffer from an epimerization process in C-5 at different rates. Butylamine-Benzylpenicilloyl conjugates (5R,6R)-Bu-BPO and (5S,6R)-Bu-BPO were selected as a simple model for mayor determinant to evaluate the role of the different epimers in the immunoreactivity with sera from penicillin-allergic patients. In vitro immunoassays indicate that any change in the chemical structure of the antigenic determinant of BP significantly affects IgE recognition. The inclusion of stereochemically pure compounds or mixtures may have important implications for both the reproducibility and sensitivity of in vivo and in vitro diagnostic tests.